2016
DOI: 10.1002/slct.201600559
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Size Sensitivity in the Hydrogen Production from Formic Acid over Carbon‐Supported Pd Nanoparticles

Abstract: The size effect in the hydrogen production from formic acid decomposition has been investigated using a series of carbonsupported Pd NPs with different particle sizes ranging from 2.7 to 5.5 nm. A volcano type relationship between catalytic activity and NPs size was obtained. This result suggests that there is an optimum relative proportion of low-and high-coordination surface atoms within a regular arrangement of the Pd NPs, which was achieved at 3.9 nm in diameter under the present experimental conditions. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 70 publications
3
50
1
Order By: Relevance
“…Recently, the relationship between the Pd NP size (supported on an activated carbon material) and the H 2 output by FA decomposition has been described as a volcano plot between 2.7 and 5.5 nm of NPs average size, observing the highest activity in the FA decomposition for the Pd NPs with an average size of 3.9 nm. 41 iii)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the relationship between the Pd NP size (supported on an activated carbon material) and the H 2 output by FA decomposition has been described as a volcano plot between 2.7 and 5.5 nm of NPs average size, observing the highest activity in the FA decomposition for the Pd NPs with an average size of 3.9 nm. 41 iii)…”
Section: Resultsmentioning
confidence: 99%
“…34,35 The incorporation of Pd NPs on different supports (carbon, zeolites, MOFs or silica) has also been studied in the literature with different results depending on the nature of the support and the active phases features. [36][37][38][39][40][41] Herein the evolution of the PVP-Pd interaction over time as well as its repercussion on the final catalytic performance in the H 2 production from the dehydrogenation of FA was assessed by synthesising a series of catalysts based on PVP-capped Pd NPs supported on a meso-and macroporous SiO 2 . To this end, NPs with different PVP/Pd molar ratios and aging times were used.…”
Section: Introductionmentioning
confidence: 99%
“…30 Considering the lots of similarities between FA oxidation and FAD reaction, the particle size Pd is also expected to inuence the adsorption and desorption behaviors of intermediates during the FAD reaction. Moreover, in addition to the previous researches briey announcing the particle size effect, 14,21,31 the concrete effect of the Pd particle size on the activity was recently identied by Li et al, Navlani-García et al and Zhang et al [32][33][34] By adopting cuboctahedronshape model, they concluded that the enhanced interaction between positive Pd and negative charged intermediates (e.g. formate ion) due to the large portion of edge Pd in small particle size.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, the high activity of seq-impregnated catalyst is attributed to the presence of electron-decient Pd. 24,[32][33][34] The XPS result can also explain the similar activity of Pd 1 NiO 1.3 /C (co) to Pd/C despite its smaller particle size than Pd/C. Because more negative Pd in Pd 1 NiO 1.3 /C (co) than Pd/C cannot interact well with negative charged intermediates, it counteracts the promoting effect of small particle size of Pd 1 NiO 1.3 /C (co).…”
Section: Resultsmentioning
confidence: 99%
“…Generally,t he smallestp articles showed higher activity. However, in the work of Navlani-Garcíae tal., [42] the volcanotype relationship as af unctiono ft he Pd nanoparticle size, with an optimum moderate size of 3.9 nm, was associated with as uitable proportion of low-coordinated (small particles) and high-coordinated (large particles) palladium atoms. The mechanism of the FA dehydrogenation on metals and metal oxides was proposed by Mars.…”
Section: Discussionmentioning
confidence: 94%